2000
DOI: 10.1074/jbc.c000359200
|View full text |Cite
|
Sign up to set email alerts
|

Defective Heparan Sulfate Biosynthesis and Neonatal Lethality in Mice LackingN-Deacetylase/N-Sulfotransferase-1

Abstract: Heparan sulfate is a sulfated polysaccharide present on most cell surfaces and in the extracellular matrix. In vivo functions of heparan sulfate can be studied in mouse strains lacking enzymes involved in the biosynthesis of heparan sulfate. Glucosaminyl N-deacetylase/ N-sulfotransferase (NDST) catalyzes the first modifying step in the biosynthesis of the polysaccharide. This bifunctional enzyme occurs in several isoforms. We here report that targeted gene disruption of NDST-1 in the mouse results in a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(182 citation statements)
references
References 42 publications
4
178
0
Order By: Relevance
“…In contrast, the ratios of the N -deacetylation and N -sulfation activities between NDST-1 and -2 were similar (72). Notably, mice carrying a targeted disruption of NDST-2 are unable to synthesize heparin but can produce HS (73,74), whereas those of NDST-1 synthesize lowsulfated variant of HS resulting in embryonic lethality (75,76). The NDST isoforms have distinct expression levels in different mouse tissues (72).…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 88%
“…In contrast, the ratios of the N -deacetylation and N -sulfation activities between NDST-1 and -2 were similar (72). Notably, mice carrying a targeted disruption of NDST-2 are unable to synthesize heparin but can produce HS (73,74), whereas those of NDST-1 synthesize lowsulfated variant of HS resulting in embryonic lethality (75,76). The NDST isoforms have distinct expression levels in different mouse tissues (72).…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 88%
“…For example, studies showed that N-deacetylase/N-sulfotransferase-1 (NDST1) is an essential NDSR isozyme in mouse embryonic development, 15 and disruption of NDST1, resulting in severe malformations in the lung. 16 Therefore, miR-149 was likely to affect the expression of the miRNA target gene NDST1 and contribute to the susceptibility of CWP. However, functional characterizations of SNP rs2292832 in miR-149 and its target mRNAs in CWP are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Ndst1 mutants show apparently normal lung structure but have major deficiency in surfactant production leading to neonatal lethality. Abnormal dilated lung alveolar spaces have been reported in Sulf2 2/2 mice in which HS 6-O sulfation is altered by the lack of HS sulfatase 2 (Sulf2) (Fan et al, 2000;Li et al, 2003;Lum et al, 2007;Ringvall et al, 2000).…”
Section: Organogenesis In the Absence Of Hs6st1mentioning
confidence: 99%